The role of Facebook food-ordering chatbots on the perceived brand preference of online customers in Tacloban City - Daño, Julianne P.; Dioso, Charlene Jade I.; Ebio, Allen A.; Olojan, Cyramae F.
This research investigates the role of Facebook food-ordering chatbots on the perceived brand preference of online customers in Tacloban City. Facebook food-ordering chatbots provides local businesses with an innovative approach to engage with their online customers and streamline the process of food ordering. With the city's food industry booming and more customers going online, understanding these chatbots is crucial as its role in brand preference remains unclear. This study therefore aims to identify key factors influencing the use of chatbots, determine factors affecting brand preference, explore the relationship between these factors, and generate new indicators. A sample size of 150 respondents were gathered through purposive sampling technique. Utilizing a mixed-method convergent parallel design, quantitative data were gathered through 5-point Likert scale surveys, and qualitative insights were obtained via open-ended questions. Confirmatory factor analysis, descriptive analysis, and structural equation modeling, and thematic analysis were employed for data analysis. Findings indicate that anthropomorphic, problem-solving. user interface, trust, and satisfaction significantly influence chatbot usage. Brand preference is primarily driven by performance/quality value, price value, emotional value, and social value. The one-way directional relationship revealed strong links between chatbot-use factors and brand preference factors, while the qualitative data led to the identification of new indicators affecting the two sets of factors. This comprehensive framework offers valuable insights for analyzing consumer behavior as well as for enhancing chatbot implementation and brand strategies in Tacloban City's online food industry.